TEACHING WRITING THROUGH THINK, TALK, WRITE (TTW) TECHNIQUES FORJUNIORHIGH SCHOOL LEVEL - Nurfisi Arriyani; Videla Sari (HOLISTICS, 2019)
Think-Talk-Write is one of learning strategieswhich purposes to improve students’ understanding ability.This strategy can minimize the students’ difficulties in writing and help the teacher in teaching writing. In other words, Think-Talk-Write can help students construct their own knowledge. So that, the students understandtheconcept better. Students are also able to communicate or discuss their thought with their friends. So, the students can help each other and exchange their ideas. This strategy can help students to understand the material being taught. It is possible thing, if they are already familiar with the material obtained, they will be easy to apply their idea in writing or in this case, students are able to make narrative text. Thus, this researchwas done to see whether Think-Talk-Write techniques gives contribution to improve the students’ motivation in writing narrative text at Junior High Schoollevel. It was found that teaching process ran well. Students were active, enthusiastic and interested in writing. The result of research showed that Think-Talk-Write techniques can improve students’ achievement in writing narrative text.